Non-carcinogenic health risks of fluoride exposure in minors based on national surveillance in China, 2014 and 2018 - Liu Yang; Mang Li; Junrui Pei; Lijun Zhao; Wei Wei (Scientific Reports)
Abstract High fluoride concentrations in groundwater represent a substantial global public health concern. In China, over 70 million individuals suffer from drinking water fluorosis. This study reports national surveillance data in 2014 and 2018, dividing affected areas into six regions. The compliance rate for safe fluoride concentrations in drinking water improved by 13.1%. The data revealed a statistically significant difference in fluoride concentration between areas that underwent improvements and those that did not (Z = − 10.583, P < 0.001). The potential health risks for minors were evaluated, with hazard index (HI) values for minors exceeding 1, indicating the possibility of non-carcinogenic health risks associated with fluoride exposure. Furthermore, in certain regions, the non-carcinogenic health risks related to the current Chinese national standard for fluoride in drinking water (1.0 mg/L) for infants have surpassed the acceptable threshold. The implementation of improvement initiatives led to a reduction in the non-carcinogenic risk of fluoride exposure for minors, with odds ratios (95% CI) for infants, children, and teens were 0.369 (0.268, 0.509), 0.556 (0.452, 0.683), and 0.823 (0.740, 0.914), respectively. These findings can assist governmental agencies in formulating more effective policies for the protection of minors, particularly infants, from fluoride exposure.